Seismic anisotropy indicates organised melt beneath the Mid-Atlantic Ridge aids seafloor spreading - Kendall, J; Schlaphorst, D; Rychert, C; Harmon, N; Agius, M; Tharimena, S (Geological Society of America, 2023)
Skip Nav Destination RESEARCH ARTICLE| AUGUST 04, 2023 Seismic anisotropy indicates organized melt beneath the Mid-Atlantic Ridge aids seafloor spreading J.M. Kendall; D. Schlaphorst; C.A. Rychert; N. Harmon; M. Agius; S. Tharimena Author and Article Information Geology (2023) 51 (10): 968–972. https://doi.org/10.1130/G51550.1 Article history Standard View Open thePDFfor in another window Cite Share Icon Share Permissions Abstract Lithospheric plates diverge at mid-ocean ridges and asthenospheric mantle material rises in response. The rising material decompresses, which can result in partial melting, potentially impacting the driving forces of the system. Yet the geometry and spatial distribution of the melt as it migrates to the ridge axis are debated. Organized melt fabrics can cause strong seismic anisotropy, which can be diagnostic of melt, although this is typically not found at ridges. We present anisotropic constraints from an array of 39 ocean-bottom seismometers deployed on 0–80 Ma lithosphere from March 2016 to March 2017 near the equatorial Mid-Atlantic Ridge (MAR). Local and SKS measurements show anisotropic fast directions away from the ridge axis, which are consistent with strain and associated fabric caused by plate motions with short delay times, δt (<1.1 s). Near the ridge axis, we find several ridge-parallel fast splitting directions, φ, with SKS δt that are much longer (1.7–3.8 s). This is best explained by ridge-parallel sub-vertical orientations of sheet-like melt pockets. This observation is much different than anisotropic patterns observed at other ridges, which typically reflect fabric related to plate motions. One possibility is that thicker sub-ridge lithosphere with steep sub-ridge topography beneath slower spreading centers focuses melt into vertical, ridge-parallel melt bands, which effectively weakens the plate. Associated buoyancy forces elevate the sub-ridge plate, providing greater potential energy and enhancing the driving forces of the plates.